MITOS DI NUSA PENIDA ANALISIS STRUKTUR, FUNGSI, DAN MAKNA - Sudiasih, Ni Putu (Humanis; Volume 15. No.2. Mei 2016)
This study discusses the myth in Nusa Penida Analysis of Structure, Function and Meaning. These myths come from Nusa Penida. The aim of this title in anataranya is (1) because studies have not been investigated (2) because this myth comes from the village itself. Myth in Nusa Penida Structural Analysis, Function and Meaning analyzed using structural theory and the theory of semiotics. Structural theory relates to the structure at the level of literary works (intrinsic), and the level of the system is contained in a myth in Nusa Penida Analysis of Structure, Function and Meaning. The theory uses a combination of several literary expert opinion including Luxemburg, Kutha Ratna, Sukada, Warren & Wellek. The method used can be divided into three stages, namely the first, phase data provision, in this first phase of the literal translation method is used idiomatically continued by using read something about assisted with recording techniques. Second, the data processing stage, in this stage of the method used descriptive analytic assisted with recording techniques, and the third is the stage of presentation of the data analysis at this stage is used informal methods. Disclosure structure in Myth in Nusa Penida Structural Analysis, Function and Meaning include: flow, incident, style, character and characterization. Myth semiotic analysis in Nusa Penida include elements of function and meaning contained in the myth. Functions include: preservation of culture, tardisi hereditary, social communities, and tolerance. While the significance include: belief system.
Keywords: myth, shape, function, and meaning